From Caterpillars to Butterflies: Exploring Pre-service Teachers’ Transformations While Navigating Global Citizenship Education - Lourenço, Mónica (Frontiers in Education, 2021)
Global citizenship education (GCE), which aims to empower learners to become proactive contributors to a more sustainable world, has recently emerged as one of the educational priorities of the 21st century. However, according to recent research, GCE is not yet embedded in teachers’ practice in a systematic manner, remaining an optional choice for willing and able teachers. Within this framework, this paper reports on a multiple case study conducted with a group of pre-service teachers (PSTs) in Portugal who were introduced to GCE in the third and final year of an undergraduate degree in Elementary Education. The study aimed to understand whether, how and to what extent the teacher education program contributed to PSTs’ professional development. Data consisted of individual reflections written by the PSTs throughout an academic year. These were analyzed thematically using grounded theory to formulate an original framework inspired by the butterfly’s metamorphosis. Results show that the experience with GCE was positive in developing PSTs’ professional knowledge and in helping them (re)construct their “becoming” teacher identities, albeit to different degrees. Implications of the results for teacher education programs are discussed.